Learning Puppet - Thompson, Chad (Infinite Skills, 2015)
"In this Learning Puppet training course, expert author Chad Thompson will teach you how to write and apply Puppet code. This course is designed for the absolute beginner, meaning no previous experience with Puppet is required.You will start by learning about the Puppet infrastructure, including Puppet agents and masters, then jump into the Puppet run cycle. From there, Chad will teach you about the Puppet language, including how to apply a simple Puppet manifest, Puppet types, and applying conditional logic in Puppet. This video tutorial also covers how to organize a Puppet environment, report with Puppet, and MCollective. Finally, you will learn about additional tools, such as external node classifiers and reporting with the Puppet dashboard.Once you have completed this computer based training course, you will be fully capable of writing and applying your own Puppet code. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.